The crisis in the Ukrainian machine-tool building 1918–1932 yrs. - N. G. Annenkova (History of science and technology, 2015)
This article analyzes the general state of scientific and technical potential of the domestic machine-tool industry in the years 1918-1932. Determined that during this period its components have undergone significant transformations of quantitative and qualitative parameters. From 1918 to 1921 they were reduced to the minimum that has led the industry to a complete paralysis. In 1925-1926 yrs. began the process of restoration of the scientific and technical potential of Ukrainian machine-tool industry, so that by 1932 the industry received facilities, comparable to pre-crisis. Established that the main cause of the branch's crisis was that state economic government agencies didn't have a comprehensive industrialization program for the country.